Farmers' knowledge, perceptions, and management practices of the new invasive pest, fall armyworm (Spodoptera frugiperda) in Ethiopia and Kenya. Issue 1 (2nd January 2019) - Kumela, Teshome; Simiyu, Josephine; Sisay, Birhanu; Likhayo, Paddy; Mendesil, Esayas; Gohole, Linnet; Tefera, Tadele
ABSTRACT: This paper reports for the first time on farmers' knowledge, perceptions and management practices of the fall armyworm ( Spodoptera frugiperda ) in Ethiopia and Kenya. A survey of 343 smallholder maize farmers was conducted. Most farmers in Ethiopia and Kenya had knowledge about fall armyworm; they could identify it mainly during its larval stage. Furthermore, most farmers in Ethiopia (93%) and Kenya (97%) encountered damage by fall armyworm in their farms. They estimated an average of 32% crop damage in Ethiopia and 47.3% of crop damage in Kenya, with an estimated yield reduction between 0.8 to 1 tonnes/ha. Nearly half of the farmers relied on chemical insecticides to control this pest. The majority (60%) of the farmers in Kenya perceived that insecticides were not effective in controlling fall armyworm as compared to most farmers (46%) in Ethiopia who perceived that chemical spray is effective for the control of fall armyworm. In Ethiopia, 26% of the farmers combined handpicking larvae with insecticide sprays, whilst 15% of the farmers practiced only handpicking. The present study highlights the need to develop management strategies for fall armyworm based on farmers' needs and priorities.